Compensatory Increase of Serum Hepassocin Protects Hyperthyroidism-Induced Hepatic Dysfunction - Wang, Chih-Chen; Lin, Ching-Han; Chou, Hsuan-Wen; Wang, Chung-Teng; Liang, Yu-Cheng; Wu, Hung-Tsung; Ou, Horng-Yih (Biomedicines, 2023)
Hepatic dysfunction is commonly observed in subjects with hyperthyroidism. Hepassocin is a hepatokine playing an important role in metabolic diseases and exhibiting a hepatic protective effect. Nevertheless, the relationship between hepassocin and hyperthyroidism was still unknown. In the present study, a total of 36 subjects with Graves’ disease were enrolled, and we found that the alanine aminotransferase (ALT) levels were significantly decreased in parallel with the decrement in serum hepassocin concentrations at 6 months after standard treatment for hyperthyroidism. In addition, HepG2 cell line was used to investigate the role of hepassocin in hyperthyroidism-induced hepatic dysfunction. Treatment of hepassocin recombinant protein in HepG2 cells dose-dependently decreased triiodothyronine (T3)-induced ALT and aspartate aminotransferase (AST) elevation. Moreover, hepassocin significantly increased the expression of phosphoenolpyruvate carboxykinase (PEPCK) in a dose-dependent manner. Deletion of hepassocin in HepG2 cells reversed the effects of T3 on PEPCK expressions. Furthermore, we found that T3 increased the expression of hepassocin through a hepatocyte nuclear factor 1α-dependent pathway. Taken together, these results indicated a compensatory increase in serum hepassocin might have a protective role in hyperthyroidism-induced hepatic dysfunction.